Dementia with lewy bodies: GBA1 mutations are associated with cerebrospinal fluid alpha‐synuclein profile. Issue 7 (12th June 2019) - Lerche, Stefanie; Machetanz, Gerrit; Wurster, Isabel; Roeben, Benjamin; Zimmermann, Milan; Pilotto, Andrea; Preische, Oliver; Stransky, Elke; Deuschle, Christian; Hauser, Ann‐Kathrin; Schulte, Claudia; Lachmann, Ingolf; et al.
Abstract: Background: Patients with dementia with Lewy bodies reveal a variable pathology including alpha‐synuclein, amyloid‐beta, and Tau. Mutations in GBA1 are specifically associated with synucleinopathies. PD patients with GBA1 mutations show reduced CSF levels of total alpha‐synuclein. Objective: Whether GBA1 mutations are associated with a CSF alpha‐synuclein profile in dementia with Lewy bodies. Methods: Screening of the GBA1 gene and single‐nucleotide polymorphisms in SNCA rs356220, APOE rs429358, and MAPT rs1052587 as well as CSF levels of total alpha‐synuclein, amyloid‐beta1‐42, total‐Tau, phospho‐Tau, and neurofilament light chain were assessed in 100 dementia with Lewy bodies and 39 controls cross‐sectionally. Results: Severity of GBA1 mutations was associated with a younger age at onset and higher prevalence of rapid eye movement sleep behavior disorder. CSF levels of total alpha‐synuclein were lowest in DLBGBA_pathogenic compared to DLBGBA_mild and DLBGBA_wildtype . Conclusion: Similar to PD, pathogenic GBA1 mutations seem to be associated with CSF alpha‐synuclein profiles in dementia with Lewy bodies. That might be useful for patient stratification for specific alpha‐synuclein–lowering compounds. © 2019 International Parkinson and Movement Disorder Society